Washed microbiota transplantation: candidates for a novel strategy for ameliorating autism spectrum disorder - Feng, Shuo; Wang, Jiangyan; Si, Xinyu; Lu, Shenghua; Lu, Caimei; Gao, Zheng; Yang, Juan; Wu, Jiali; He, Xingxiang; Wu, Lei (Frontiers in Microbiology, 2025)
Autism Spectrum Disorder (ASD) is a severe neurodevelopmental disorder with an increasing global incidence, imposing substantial burdens on both society and affected families. The pathogenesis of ASD is complex, involving genetic, environmental, and other factors. Notably, children with ASD often exhibit gut microbiota dysbiosis, and the relationship between gut microbiota and ASD has garnered growing attention. Current treatments for ASD remain limited and unsatisfactory. As an emerging therapeutic approach, Washed Microbiota Transplantation (WMT) reduces undigested food residues, fungi, parasite eggs, and pro-inflammatory metabolites, thereby lowering the incidence of adverse clinical events. WMT also addresses ethical and aesthetic concerns associated with Fecal Microbiota Transplantation (FMT), enhances treatment safety, and offers new hope for ASD management. This review integrates global literature to analyze the latest findings on ASD epidemiology, societal impacts, existing therapies, and clinical research on WMT, aiming to provide scientific evidence for the clinical application of WMT in ASD treatment.